Pengaruh Servant Leadership dan Empowerment terhadap Organizational Citizenship Behaviour pada PT. Samaja Bali Villa - A.A Ngurah Yoga Indra Pratama; I Wayan Sujana; Ni Nyoman Ari Novarini (Forum Inovasi Bisnis dan Manajemen, 2020)
Organizational Citizenship Behavior is a form of behavior which is an individual choice and initiative, not related to the formal reward system of the organization but in aggregate to increase organizational effectiveness. This behavior shows the added value of employees which is a form of prosocial behavior, namely social behavior that is positive, constructive and means helping. This research was conducted at PT. Samaja Bali Villa, with the research object Servant Leadership and Empowment on Organizational Citizenship Behavior. The population in this study were employees of PT. Samaja Bali Villa. The sample of this study was determined by the Simple Random Sampling method, so that the number of samples was 47 people. The data analysis technique used is multiple linear regression analysis. In addition, in this study, a classic assumption test was also carried out which included tests of normality, heteroscedasticity and multicollinearity. The test results show that Servant Leadership has a positive and significant effect on Organizational Citizenship Behavior at PT. Samaja Bali Villa. Empowerment has a positive and significant effect on Organizational Citizenship Behavior at PT. Samaja Bali. Based on the average score on the servant leadership variable where overall respondents have the least perception of the leadership statement items encouraging the achievement of progress and development for the company, it is better if the leadership of PT. Samaja Bali Villa is able to motivate and create a pleasant working atmosphere. So, it is hoped that it can foster employee responsibility at work in order to achieve maximum company goals. Based on the average score on the empowerment variable where overall respondents have the smallest perception of items that respect the abilities possessed by employees, the leadership of PT Samaja Bali Villa needs to give employees the right or authority to plan, control and make decisions on jobs that have become their responsibility, so that employees are able to become independent and show their best performance.